Flow and enjoyment: Music listening experience between musicians and non-musicians / Soon Wan Fei - Soon , Wan Fei (2019)
This intrinsic qualitative case study has been conducted to understand more about the Flow experience resulting from music listening as suggested by Csikszentmihalyi (1990). The Flow experience is a state in which “people are so involved in something so deeply that nothing else seems to matter” (Csikszentmihalyi, 1997). Scientists and neurologists have found that there are different brain functions and structures between musicians and non-musicians. Therefore, music might work differently on musicians and non-musicians, and it might affect their Flow experiences. However, there are some scholastic gap in the study of relationships between music listening and the Flow experiences among musicians and non-musicians. Hence, this research tends to find out musicians’ and non-musicians’ Flow experiences in music listening, and their listening enjoyment experiences. A total of four classically-trained musicians and four non-musicians participated in this study. They have done in-depth interviews to discuss their feelings of enjoyment and Flow experiences while they were listening to music. Data collected had been analysed, be coded, be categorised and be evaluated by using within-case and across-case approaches. Evidence shown that some data supported Csikszentmihalyi’s nine dimensions of the Flow model in music listening, but some are not. There are six characteristics of Csikszentmihalyi’s Flow model which fits in the music listening Flow. Besides that, musical preference, familiarity, and meaningfulness in music listening are also the factors which can affect participants’ Flow experience. Furthermore, it is found that the autotelic personality, reflection, escapement, and the autonomy sense of control are the factors which lead music listening Flow to the listeners’ enjoyment. At last, a model has been proposed at the end of the findings.